The strategy of state information of the creation of Lithuania's image in the world - Gudauskas, Renaldas (Information & Media, 1997)
The article deals with the problems of the creation of Lithuania's image in the world and proposes solving them using the methods of the Information and Communication sciences. The possibilities of conceptually and positively exposing the country to the international public are analysed. The creation of the consistent international network of communication is seen as a necessary means by which to timely distribute worldwide State strategic announcements about the most important events in Lithuania.
Keywords: -